Helminth infection modulates systemic pro-inflammatory cytokines and chemokines implicated in type 2 diabetes mellitus pathogenesis - Rajamanickam, Anuradha; Munisankar, Saravanan; Dolla, Chandrakumar; Menon, Pradeep A.; Thiruvengadam, Kannan; Nutman, Thomas B.; Babu, Subash (PLOS Neglected Tropical Diseases, 2020)
Background The prevalence of helminth infections exhibits an inverse association with the prevalence of Type 2 diabetes mellitus (T2DM), and helminths are postulated to mediate a protective effect against T2DM. However, the biological mechanism behind this effect is not known. Aims/Methods We postulated that helminth infections act by modulating the pro-inflammatory cytokine and chemokine milieu that is characteristic of T2DM. To examine the association of cytokines and chemokines in helminth-diabetes co-morbidity, we measured the plasma levels of a panel of pro-inflammatory cytokines and chemokines in individuals with Strongyloides stercoralis infection (Ss+) and T2DM at the time of Ss diagnosis and then 6 months after definitive anthelmintic treatment along with uninfected control individuals with T2DM alone (Ss-). Principal findings Ss+ individuals exhibited significantly diminished levels of the pro-inflammatory cytokines–IL-1α, IL-1β, IL-6, IL-12, IL-18, IL-23, IL-27, G-CSF and GM-CSF and chemokines–CCL1, CCL2, CCL3, CCL11, CXCL1, CXCL2, CXCL8, CXCL9, CXCL10 and CXCL11. In contrast, Ss+ individuals exhibited significantly elevated levels of IL-1Ra. Anthelmintic treatment resulted in increased levels of all of the cytokines and chemokines. Conclusions Thus, helminth infections alleviate and anthelmintic therapy partially restores the plasma cytokine and chemokine levels in helminth-diabetes co-morbidity. Our data therefore offer a plausible biological mechanism for the protective effect of helminth infections against T2DM.